2012
DOI: 10.1038/ismej.2012.56
|View full text |Cite
|
Sign up to set email alerts
|

Lake microbial communities are resilient after a whole-ecosystem disturbance

Abstract: Disturbances act as powerful structuring forces on ecosystems. To ask whether environmental microbial communities have capacity to recover after a large disturbance event, we conducted a whole-ecosystem manipulation, during which we imposed an intense disturbance on freshwater microbial communities by artificially mixing a temperate lake during peak summer thermal stratification. We employed environmental sensors and water chemistry analyses to evaluate the physical and chemical responses of the lake, and bar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
184
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(209 citation statements)
references
References 57 publications
23
184
2
Order By: Relevance
“…The experimental results with lake epilimnion microbial communities (26,(48)(49)(50)(51) also support scenario A. Generally, lake mixing increases nutrient input to the nutrient limited epilimnion (50), which should stimulate microbial diversity.…”
Section: Consistency Between Experimental Results and Theoretical Presupporting
confidence: 69%
See 1 more Smart Citation
“…The experimental results with lake epilimnion microbial communities (26,(48)(49)(50)(51) also support scenario A. Generally, lake mixing increases nutrient input to the nutrient limited epilimnion (50), which should stimulate microbial diversity.…”
Section: Consistency Between Experimental Results and Theoretical Presupporting
confidence: 69%
“…Several studies have also examined the resilience of lake microbial communities after disturbances (26,(48)(49)(50)(51). The experimental results with lake epilimnion microbial communities (26,(48)(49)(50)(51) also support scenario A.…”
Section: Consistency Between Experimental Results and Theoretical Prementioning
confidence: 63%
“…However, previous experiments on P. parvum invasion processes showed that communities in large (1,570-L) enclosures and small (2-L) microcosms presented no significant differences in plankton dynamics for longer periods than those encompassed by our experiment (30). Furthermore, the difference between days was probably also caused by medium-term responses of the community to initial environmental changes because stabilization of communities in response to disturbances is a continuous process that can extend for longer periods than those covered by our incubation period (33).…”
Section: Discussionmentioning
confidence: 61%
“…Microbial diversity is not resilient to all types of disturbance In this study, it is demonstrated that (1) the operational parameter SRT can selectively enrich for organisms based on life-history strategy (that is, selection of r-K-strategists); (2) in contrast to studies that show resilience of microbial diversity to pulsedisturbances (Shade et al, 2012), microbial communities in activated sludge did not fully recover to their original state after the press disturbance and (3) the recovery of microbial composition is not a prerequisite for the recovery of general ecosystem functions. Concordantly, our results support the functional redundancy hypothesis for microbial ecosystems (Allison and Martiny, 2008) and indicate that after a major disturbance, new microbial communities reassemble to perform the same ecosystem functions.…”
Section: Discussionmentioning
confidence: 80%